Pelestarian Potensi Alat Musik Kolotik Sebagai Ikon Desa Beber Ciamis - Adiwisastra, Miftah Farid; Iskandar, Yudi; Safitri, Lintang Juwita; Fauziah, Ari Zainal; Mujahidillah, Vidi Azzahra; Sulaeman, Sulaeman (Abditeknika Jurnal Pengabdian Masyarakat, 2023)
Sesuai dengan judul program pengabdian masyarakat ini, kegiatan yang dilakukan adalah Pelestarian Potensi Alat Musik Kolotik Sebagai Ikon Desa Beber Ciamis untuk para generasi muda di Desa Beber. Adapun tujuan pengabdian masyarakat ini adalah untuk mengenalkan dan melestarikan “Kolotik” kepada generasi muda, karena generasi muda jaman sekarang lebih memilih kesenian dan kebudayaan orang barat. Materi yang diberikan antara lain pemaparan materi tentang sejarah Kolotik dan praktik pembuatan Kolotik. Capaian kegiatan pengabdian ini adalah terlaksananya Pelestarian Potensi Alat Musik Kolotik dengan jumlah peserta kurang lebih 50 orang yang dapat mengikuti sampai akhir acara dan peserta mendapatkan pengetahuan tentang sejarah Kolotik dan praktik pembuatan Kolotik untuk meningkatkan kesadaran akan pelestarian potensi alat musik Kolotik di desa Beber.   In this era of globalization, traditional musical instruments seem to be inferior to foreign cultures that have entered Indonesia, little by little causing Indonesian people to abandon traditional musical instruments. That doesn't mean we can't listen to music other than traditional Indonesian music, but we also have to take the time to appreciate and try so that people can preserve traditional Indonesian musical instruments. The Kolotik musical instrument is a traditional musical instrument originating from Ciamis Regency with the main ingredients being coconut shells and bamboo. The sound that sounds unique makes this musical instrument often used as a souvenir from Cimaragas District, to be precise in Beber village. The purpose of this dedication is to introduce and preserve "Kolotik" to the younger generation, because today's young generation prefers western art and culture. The expected results of this activity are that the younger generation can get to know Kolotik as a musical instrument that was created in the Beber village and also increase the awareness of the younger generation about the arts in their surroundings. They are also moved to support cultural preservation and help protect local culture and participate when there are activities in the framework of cultural preservation, teach that culture to future generations so that the culture is not destroyed and can still survive, Love their own culture without demeaning and harassing the culture of others.